Integrated framework of district cooling system for commercial buildings - Zamhuri, Muhammad Ikhwan (2021)
Malaysia is situated in the latitude of -6.2 degree and longitude of 106.8 degree with average summer dry and wet bulb temperature of 32.2°C and 32.7°C, thus the use of air conditioning system is crucial to tackle the climate condition. Chilled water air conditioning system is widely used to supply cooling in large capacity for industrial process and commercial buildings. Nevertheless, air conditioner consumes more than 60% of electricity consumption in buildings. District cooling system (DCS) technology comprising of a central chiller plant provides advantage compared to local air conditioning system. DCS has higher efficiency, uses less power for the system to be operated, provides more usable space on buildings, and can be operated with minimum amount of manpower while handling the same amount of cooling load. Additionally, this system can be combined with thermal energy storage and provided lower operational cost. This study developed a new systematic framework and methodology based on pinch analysis for designing DCS integrated with ice thermal storage (ITS). The cooling system cascade analysis (COSCA) is constructed to determine the optimal size of the chiller and ITS. Economic and environmental analysis was performed by calculating the payback period and return on investment using Microsoft Excel Trend function. A sensitivity analysis test was performed by using the Microsoft Excel Table function. However, pinch analysis has a few limitations. To be more holistic, a mathematical model was developed by using the general algebraic modelling system (GAMS) for optimisation of DCS to determine the minimum total energy cost, optimal capacity of DCS equipment and renewable energy (RE) and electricity consumption in order to minimise the economic and environmental effects. The methodology has been demonstrated for commercial building, consisting of 5 main buildings (mall, hotel and cinema) with daily cooling demand requirement of 66,284 refrigerant tonne hour (RTH). The results from the case study revealed that the optimal capacity of the chiller was 3069 refrigerant tonne (RT), ice tank was rated 989 RT, and ice tank capacity was 9894 RTH which showed saving of annual electricity purchase cost to 9% compared to centrifugal system only (without ITS). The programming mathematical model in GAMS revealed that the DCS equipment which were electric chiller and absorption chiller with RE source has been selected to meet the cooling demand requirement with total cost leading up to 72% savings, equivalent to RM 4,846,540 as compared to the baseline. Based on these results, the system designed under the time of use or enhanced time of use tariff scheme was found to give no significant impact. Instead, the system with a RE source is selected. The sensitivity analysis revealed that the capital expenditure and operational expenditure were highly sensitive and affected the system feasibility. This framework could be used as evidence based policy making to determine financial incentive or subsidies to make DCS with RE competitive in the market. In addition, the framework is also beneficial for plant owners and engineers to choose the optimal capacity of DCS equipment, including RE, for efficient operation which accounts for supply and demand sides.